2022
DOI: 10.1039/d2tc01905a
|View full text |Cite
|
Sign up to set email alerts
|

Active-matrix micro-light-emitting diode displays driven by monolithically integrated dual-gate oxide thin-film transistors

Abstract: We present the first monolithic fabrication of a-IGZO TFTs on a GaN-based micro-LED array at a low temperature to overcome the weak thermal endurance constraint of the organic planarization layer for high resolution and stable low-cost LED displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The resulting OTFTs exhibit superior performance of milliampere driving current, low leakage current and large ON/OFF current ratio approaching 10 10 with excellent uniformity and reliability. AM micro-LED displays are finally demonstrated, with the highest resolution of 254 PPI and the highest brightness >150k nits, which are the best results so far among all reported TFT-driven AM micro-LED displays 13 , 14 , 16 19 , 31 .…”
Section: Introductionmentioning
confidence: 81%
“…The resulting OTFTs exhibit superior performance of milliampere driving current, low leakage current and large ON/OFF current ratio approaching 10 10 with excellent uniformity and reliability. AM micro-LED displays are finally demonstrated, with the highest resolution of 254 PPI and the highest brightness >150k nits, which are the best results so far among all reported TFT-driven AM micro-LED displays 13 , 14 , 16 19 , 31 .…”
Section: Introductionmentioning
confidence: 81%
“…Monolithic displays with various backplane technologies, such as organic thin-film transistors (TFTs) and amorphous oxide TFTs, have been reported in the literature. 1,2 Herein, we expand on the work performed by Yang et al, 2 which demonstrated the first monolithically integrated LED display with an indium gallium zinc oxide (IGZO) backplane by fabricating a similar device and performing a more comprehensive system-level performance characterization.…”
Section: Introductionmentioning
confidence: 99%
“…The study of monolithically integrated LED displays is a research area of growing interest. Monolithic displays with various backplane technologies such as organic thin-film transistors (TFTs) and amorphous oxide TFTs have been reported in the literature [1,2]. Herein, we expand on the work performed by Yang et al [2], which demonstrated the first monolithically integrated LED display with indium gallium zinc oxide (IGZO) backplane by fabricating a similar device and performing a more comprehensive system-level performance characterization.…”
Section: Introductionmentioning
confidence: 99%